Effect of Donor Age and Sex on the Outcome of Liver Transplantation - Marino, Ignazio Roberto (1995)
We correlated donor and recipient factors with graft outcome in 436 adult patients who underwent 462 liver transplants. Donor variables analyzed were age, gender, ABO blood group, cause of death, length of stay in the intensive care unit, use of pressors or pitressin, need for cardiopulmonary resuscitation, terminal serum transaminases, and ischemia time. Recipient variables analyzed were age, gender, primary diagnosis, history of previous liver transplant, ABO blood group, cytotoxic antibody crossmatch, United Network for Organ Sharing (UNOS) status, and waiting time (except for the cross-match results, they were all known at the time of the operation). The endpoint of the analysis was graft failure, defined as patient death or retransplantation. Using multivariate analysis, graft failure was significantly associated with donor age, donor gender, previous liver transplantation, and UNOS 4 status of the recipient. The effect of donor age became evident only when they were older than 45 years. Livers from female donors yielded significantly poorer results, with 2-year graft survival of female to male 55% (95% CI, 45% to 67%); female to female, 64% (95% CI, 54% to 77%); male to male, 72% (95% CI, 66% to 78%); and male to female, 78% (95% CI, 70% to 88%). The only donors identified as questionable for liver procurement were old (≥60 years) women in whom the adverse age and gender factors were at least additive. However, rather than discard even these livers, in the face of an organ shortage crisis, their individualized use is suggested with case reporting in a special category.